Reinterpreting Islamic Inheritance: Supreme Court Jurisprudence and Gender Justice in Indonesia - Roslina, Roslina; Abbas, Syahrizal; Ismail, Ilyas; Jauhari, Iman (Jurnal Ilmiah Peuradeun, 2025)
The implementation of Islamic inheritance law in Indonesia continues to face interpretive challenges in balancing classical jurisprudence with contemporary demands for gender justice. This study examines how the Indonesian Supreme Court, through landmark decisions—Decision No. 86 K/AG/1994 and Decision No. 184 K/AG/1995—has redefined inheritance principles by granting daughters the legal authority to block the inheritance rights of the testator’s siblings. Employing a normative–juridical approach that integrates statutory, conceptual, and case-based analyses, this research explores the Court’s interpretive reliance on Ibn ʿAbbās’s minority opinion concerning Qur’an 4:176, which equates the inheritance positions of sons and daughters. The findings reveal that the Court’s jurisprudence prioritizes genealogical proximity (qarābah al-dam) over gender preference, thereby reconfiguring inheritance distribution and affirming daughters as residuary heirs (ʿaṣabah). This reinterpretation represents a progressive form of ijtihād qaḍāʾī that harmonizes Islamic law with constitutional principles of equality and justice. Academically, the study contributes a contextual model for integrating maqāṣid al-sharīʿah and civic reason within Indonesia’s plural legal framework; practically, it offers a reference for reforming the Compilation of Islamic Law and advancing gender-equitable inheritance jurisprudence across Muslim-majority societies.